MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA PERAWAT MENGGUNAKAN HAZARD IDENTIFICATION RISK ASSESSMENT AND RISK CONTROL DI RUANG RAWAT INAP RSUD KHIDMAT SEHAT AFIAT KOTA DEPOK - Subagja Dwi Permana (2023)
Nurses when providing nursing care are inseparable from the occurrence of work accidents, such as needle sticks and falls. The purpose of the study was to determine OHS risk management using Hazard Identification Risk Assessment and Risk Control on Nurses at Khidmat Sehat Afiat Hospital, Depok City. The research design uses a mix method and the data collection methods used are observation and interviews. Informants in the study amounted to 5 people, namely 3 heads of rooms and 2 team leaders. Quantitative data using descriptive analysis. The results showed that there were 7 nurse work activities identified as having potential hazards, namely the possibility of contamination and contracting patient diseases, musculoskeletal injuries and physical injuries. Risk assessment obtained one extreme risk work activity (14.28%), four high risk work activities (57.14%), two low risk work activities (28.57%). Qualitative analysis using Colaizi to get the main themes. The results obtained there are 3 main themes, namely the causes of work accidents; risks that may occur to nurses due to work; and prevention efforts that have been implemented by the hospital. The conclusion is that nurses must work according to procedures, use the right PPE and prioritize work safety to avoid the risk of work accidents. It is expected that superiors supervise nurses regularly in implementing work safety.